Linking warming effects on phenology, demography, and range expansion in a migratory bird population. - Alves, José A; Gunnarsson, Tómas G; Sutherland, William J; Potts, Peter M; Gill, Jennifer A (Wiley, 2019)
Phenological changes in response to climate change have been recorded in many taxa, but the population-level consequences of these changes are largely unknown. If phenological change influences demography, it may underpin the changes in range size and distribution that have been associated with climate change in many species. Over the last century, Icelandic black-tailed godwits (Limosa limosa islandica) have increased 10-fold in numbers, and their breeding range has expanded throughout lowland Iceland, but the environmental and demographic drivers of this expansion remain unknown. Here, we explore the potential for climate-driven shifts in phenology to influence demography and range expansion. In warmer springs, Icelandic black-tailed godwits lay their clutches earlier, resulting in advances in hatching dates in those years. Early hatching is beneficial as population-wide tracking of marked individuals shows that chick recruitment to the adult population is greater for early hatched individuals. Throughout the last century, this population has expanded into progressively colder breeding areas in which hatch dates are later, but temperatures have increased throughout Iceland since the 1960s. Using these established relationships between temperature, hatching dates and recruitment, we show that these warming trends have the potential to have fueled substantial increases in recruitment throughout Iceland, and thus to have contributed to local population growth and expansion across the breeding range. The demographic consequences of temperature-mediated phenological changes, such as the advances in lay dates and increased recruitment associated with early hatching reported here, may therefore be key processes in driving population size and range changes in response to climate change.